A Critical Appreciation to Thomas Groome's Shared Praxis Approach - Sutrisna Harjanto (Asosiasi Teolog Indonesia, 2016)
Thomas Groome’s shared Christian praxis approach is the fruit of a genius effort to draw theological, philosophical, and pedagogical insights from various, sometimes opposite, resources, and blend them together to provide a rich approach in Christian religious education. His approach can be understood better by exploring the theological and the philosophical frameworks behind it, and also the historical background that influences Groome, which shaped his thoughts and to which he reacted. Among the significant contributions of this approach are an enriched epistemology for Christian religious education and a balance/holistic approach between theory and praxis, and between Christian Story/Vision and participant’s stories/vision. There are, however, some points that need to be critically challenged in order to make this approach more fruitful, such as his overemphasis of freedom as the purpose of Christian religious education and the absence of clearer boundary markers between the constitutive and nonconstitutive elements of the Christian Story/Vision in this approach.